Answer:
if f(x)= -4x+3
f(-5)= 23
Step-by-step explanation:
first you substitute x for -5
f(-5)= -4(-5)+3
then you multiply
-4(-5)
f(-5)=20+3
you get the positive 20 because negative times negative equals positive
then you just add the rest (20+3) which will give you your answer
f(-5)= 23
Answer:
the answer for X is -6
Step-by-step explanation:
g(X)=5/2x -1 and g(X)= - 1
sub -16 on g(X)
-16=5/2x -1
-16+1 = 5/2x
-15 = 5/2x
divide both sides by 5/2
X= -6
Answer:
-240
Step-by-step explanation:
500 - 800 + 60
= -300 + 60 = -240
Answer:
.12314
Step-by-step explanation:
F(1) = -2
hope it helps
---------------------------------